The art of hardware architecture : design methods and techniques for digital circuits. - Arora, Mohit, ....- (New York : Springer, 2012)
This book highlights the complex issues, tasks and skills that must be mastered by an IP designer, in order to design an optimized and robust digital circuit to solve a problem. The techniques and methodologies described can serve as a bridge between specifications that are known to the designer and RTL code that is final outcome, reducing significantly the time it takes to convert initial ideas and concepts into right-first-time silicon. Coverage focuses on real problems rather than theoretical concepts, with an emphasis on design techniques across various aspects of chip-design. Describes techniques to help IP designers get it right the first time, creating designs optimized in terms of power, area and performance;Focuses on practical aspects of chip design and minimizes theory;Covers chip design in a consistent way, starting with basics and gradually developing advanced concepts, such as electromagnetic compatibility (EMC) design techniques and low-power design techniques such as dynamic voltage and frequency scaling (DVFS).Mohit Arora is a Senior Systems Engineer with Freescale Semiconductor. Since joining Freescale in 2005, his responsibilities have included developing systems and architecture requirements and leading the development of VoIP-based SOCs, as well as generic microcontroller SOCs. As a systems engineer, he has been involved in product definition and writing specification, working on MCU/MPU-based products for the mid-high-end industrial and consumer market space. Prior to joining Freescale, he worked for Agilent Technologies, ST Microelectronics and DCM Technologies as a design engineer and lead, focused on printing ASICs, USB2.0 PHY, PCI-Express, Infiniband and Serial ATA protocols. He earned a Bachelor's degree in Electronics and Communication Engineering from Netaji Subhas Institute of Technology (NSIT), India in 2000, has more than 30 publications in international magazine and holds a patent on serial links.